Proximate and biological activity studies of Syzygium samarangense: Study of different extractives of Syzygium samarangense - Tirthankar Biswas; Md. Al-Amin; Mohammad Shoeb; Md. Kamrul Hasan; Md. Nazrul Islam; Md. Mizanur Rhaman (Current Research on Bioscences and Biotechnology, 2021)
Red and green varieties of Syzygium samarangense, commonly known as Jamrul, are very popular as seasonal fruits to all ages of people in Bangladesh. Objective of the work was chemical and biological activity studies of S. samarangense red and green varieties grown in Bangladesh. Air-dried fruits of S. samarangense were successively extracted with n-hexane, dichloromethane (DCM) and methanol. The moisture and ash content of the raw fruits were determined by thermal heating at 105 and 700℃, respectively. Different biologically important functional groups were identified by FT-IR spectroscopy. The n-hexane, DCM and methanolic extracts were tested for cytotoxicity against HeLa and Vero cell lines. Total phenolic content, total flavonoid content and total antioxidant capacity in the three extracts of both varieties were determined. The moisture content and ash content were 92% and 90%, and 0.12% and 0.16% in red variety and green variety, respectively. UV-Vis spectrum revealed the presence of long chain conjugation or polycyclic aromatic chromophores in n-hexane, DCM and methanolic extracts of S. samarangense. The DCM extract of both varieties had highest total phenolic content, flavonoid content and antioxidant capacity compared to n-hexane and methanol extracts. The study concludes that the fruit of S. samarangense (red and green variety) grown in Bangladesh are rich source of phytochemicals which possess antioxidant activity and safe to health for their non-cytotoxic properties. The green variety contains more phenolic content and antioxidant capacity than red variety.